2010
DOI: 10.4314/jtdorl.v21i1.57955
|View full text |Cite
|
Sign up to set email alerts
|

Indications des laryngoscopies en suspension

Abstract: INTRODUCTIONLes indications des laryngoscopies directes sous anesthésie générale ou laryngoscopie en suspension (LES) sont nombreuses dans un but diagnostique et/ou interventionnel (1). La LES est réalisée aux fins de diagnostic des pathologies laryngées morphologiques, neurologiques, inflammatoires et tumorales. Results : SL were performed for 147 cases (63,64%) of functional laryngeal disorders including 78 cases (33,77%) of laryngeal dyspnea and 69 cases (29,87%) of dysphonia. In 84 cases (36,36%) SL was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…Our results are close to those of Amana et al, Ette et al, who found 66.2% and 60% respectively for benign tumors [1] [7]. Papilloma was the most common histological form in the Amana et al series, accounting for 20.2% [1], compared with 16.6% in the Koffi-Aka series [4]. The results reported by some authors [3] [5] were low, at 19.70%.…”
Section: Morphological Featuressupporting
confidence: 87%
See 1 more Smart Citation
“…Our results are close to those of Amana et al, Ette et al, who found 66.2% and 60% respectively for benign tumors [1] [7]. Papilloma was the most common histological form in the Amana et al series, accounting for 20.2% [1], compared with 16.6% in the Koffi-Aka series [4]. The results reported by some authors [3] [5] were low, at 19.70%.…”
Section: Morphological Featuressupporting
confidence: 87%
“…In professional environments with limited resources, particularly in developing countries, these tumors pose a problem of diagnostic delay, often with aesthetic prejudice [4]. The aim of our study was to examine the epidemiological, clinical, therapeutic, and evolutionary particularities of these tumors, and to report on our experience in their therapeutic management in view of the limited technical resources available.…”
Section: Introductionmentioning
confidence: 99%